analysis on electromagnetic waves propagation in optical fiber using the Laasonen method finite difference approach - Radhiyah Mardhiyah (Department of Physics – Universitas Negeri Padang UNP, 2014)
Wave Nonlinear Schrodinger (NLS) is a wave that propagates in an optical fiber. NLS wave has a wave with wave propagation characteristics are stable and propagate without change of shape. This study aims to examine and analyze the behavior of wave propagation NLS with the influence wavelengths (Nλ) on its amplitude. Research conducted including the type of basic research using a numerical approach. Used numerical approach is the Finite Difference Laasonen method. Based on the generated soliton solutions, the wave nature of the NLS can be analyzed which shows that large amplitude (A) NLS waves is influenced by the wavelength (λ). Results of programming in the form of a graphic display output and modeling. Modeling results for the NLS equation wavelength waves (N=1) which is comparable to the wavelength of the amplitude values. Modeling results for the wavelength variation (N=2) also showed that the wavelength is proportional to the amplitude